Investigation on level of furans and diozins in five commonly consumed fish species. - Azlan, Azrina; Razman, Muhammad Rizal; Ramli, Norazam; Abdul Latiff, Aishah; Mohamad Nasir, Nurul Nadiah (2011)
Five commonly consumed marine fish from Straits of Malacca were studied for their level of dioxins (PCDDs) and furans (PCDFs). The fish fillets were found to contain low to moderate level of fats. Among the moderate fat content species, Plotosus spp. (Sembilang) was found to contain the highest level of total PCDDs/Fs (1.23 + 0.48 pg/g of wet weight) due to the high fat content of the species. Other species however, contain low level of PCDDs/Fs that range between 0.10-0.18 pg/g of wet weight. Generally the levels of total PCDDs/Fs in fish species determined in this preliminary study were well below the European limits and are therefore safe for human consumption.